Representasi Bullying pada Drama Korea True Beauty - Ditania Nur Fadilla; M E. Fuady (UNISBA Press, 2022)
Abstract. The Korean entertainment industry is growing rapidly to enter various countries, especially Asia, starting from the entry of films, dramas, music and even culinary. Korean drama is one that people are interested in because the storyline is always interesting and the characters are never playful, including the Indonesian people. Korean dramas often raise social issues as themes and insert messages about the reality of people's lives. True Beauty is one of the dramas that presents the issue of bullying in the school environment, this drama managed to become one of the five highest-rated dramas in 2021. Bullying, which is a form of deviant communication itself, has been an issue that has been troubling for a long time. In the surrounding environment, there are still many cases of bullying that afflict especially students. The drama True Beauty raises some of the reality about a girl with an ugly face who is always the victim of bullying at her school, packaged into a visual show with a love story flavored with a typical Korean drama. The purpose of this study is to find out the signs and meanings of connotations and denotations as well as the myths of bullying contained in the Korean Drama True Beauty. This research method uses a qualitative approach using the semiotic method of Roland Barthes' model which is seen from denotation, connotation and myth. The results of the study revealed that in the Korean Drama True Beauty there were verbal and non-verbal bullying scenes. Verbal bullying is a form of humiliation that can be seen or heard by the senses, marked by words and actions which in this drama are represented by cursing, laughing, cheering (Calling Ugly, Mandu, Red Face, Slapping, Sprinkling with dirty water, Throwing things), while Non-verbal bullying is a form of humiliation that can not be directly felt by the senses in this drama represented by the form of action (Gazes, Spreading embarrassing videos, crossing out face posters). Abstrak. Industri hiburan Korea berkembang pesat hingga masuk ke berbagai negara khususnya Asia, dimulai dari masuknya film, drama, musik bahkan kuliner. Drama Korea merupakan salah satu yang diminati masyarakat karena jalan cerita yang selalu menarik dan pemeranan yang tidak pernah main-main, tak terkecuali masyarakat Indonesia. Drama Korea sering kali mengangkat isu sosial sebagai tema dan menyelipkan pesan mengenai realita kehidupan masyarakat. True Beauty merupakan salah satu drama yang menyuguhkan isu bullying di lingkungan sekolah, drama ini berhasil menjadi salah satu dari lima drama dengan rating tertinggi tahun 2021. Bullying yang merupakan suatu bentuk komunikasi yang menyimpang sendiri sudah menjadi isu yang meresahan sejak lama, tidak menutup mata di lingkungan sekitar pun masih banyak terjadi kasus bullying yang menimpa khususnya pelajar. Drama True Beauty mengangkat sebagian dari realita mengenai seorang gadis dengan wajah jelek yang selalu menjadi korban bully di sekolahnya, dikemas kedalam sebuah tayangan visual dengan dibumbui kisah cinta khas Drama Korea. Tujuan dari penelitian ini untuk mengetahui tanda dan makna konotasi dan denotasi serta mitos dari bullying yang terdapat dalam Drama Korea True Beauty. Metode penelitian ini menggunakan pendekatan kualitatif dengan menggunakan metode semiotika model Roland Barthes yang dilihat dari denotasi, konotasi dan mitos. Hasil penelitian mengungkapkan dalam Drama Korea True Beauty terdapat adegan bullying verbal dan non verbal. Bullying verbal merupakan bentuk penghinaan yang bisa dilihat atau didengar oleh indra ditandai dengan ucapan dan perbuatan yang dalam drama ini direpresentasikan dengan memaki, mentertawakan, menyoraki (Memanggil Jelek, Mandu, Wajah merah, Menampar, Menyiram dengan air kotor, Melempar dengan barang), Sedangkan bullying non verbal merupakan bentuk penghinaan yang tidak langsung dapat terasa oleh indra dalam drama ini direpresentasikan dengan bentuk tindakan (Tatapan, Menyebar luaskan video memalukan, mencoret poster wajah).